2019
DOI: 10.1002/anie.201906017
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Hydrogen Bonding Interactions in Crosslinked Methylammonium Lead Iodide Crystals: Towards Reducing Moisture and Light Degradation Pathways

Abstract: Methylammonium lead halide perovskite-based solar cells have demonstrated efficiencies as high as 24.2 %, highlighting their potential as inexpensive and solution-processable alternatives to silicon solar cell technologies.P oor stability towards moisture,u ltraviolet irradiation, heat, and ab ias voltage of the perovskite layer and its various device interfaces limits the commercial feasibility of this material for outdoor applications.Herein, we investigate the role of hydrogen bonding interactions induced w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 56 publications
(148 reference statements)
4
63
0
Order By: Relevance
“…10 ) 43 . This evidence might support the hypothesis that hydrogen bonding plays a very important role in degradation of perovskite solar cells 55 59 , especially under high-humidity testing conditions. The next important features which affect stability are molecular weight and concentration of precursor solution.…”
Section: Resultssupporting
confidence: 85%
“…10 ) 43 . This evidence might support the hypothesis that hydrogen bonding plays a very important role in degradation of perovskite solar cells 55 59 , especially under high-humidity testing conditions. The next important features which affect stability are molecular weight and concentration of precursor solution.…”
Section: Resultssupporting
confidence: 85%
“…Fortunately, several recent studies have reported that additive engineering is an effective alternative strategy. Various additives, such as polymers, small molecules, and semiconductor molecules, have been incorporated into perovskite precursor solutions . Although additives containing N, O, and S atoms with lone pairs of electrons were found to be efficient in passivating defects in perovskite films and further enhanced charge transfer and collection, they lacked sufficient evidence to demonstrate that the defect passivation undoubtedly occurred at GBs .…”
Section: Introductionmentioning
confidence: 99%
“…The organic compound contained a benzene ring, an ammonium group (−NH 2 ), and two carboxyl groups (−COOH). The molecules could easily assemble at the GBs because the benzene ring had a high cohesive energy due to its robust structure and the strong interaction of its π–π bonds . Owing to the existence of a benzene ring, it was also facile to form a hydrophobic passivating layer that prevented the permeation of moisture along the GBs.…”
Section: Introductionmentioning
confidence: 99%
“…The organic cations in 2D perovskites have been shown to keep water molecules away from the reaction site by straining the Pb-I bond on the surface. [48][49][50][51][52][53] In addition, the new structure incorporating diammonium ions is more conducive to charge transport because the distance between the inorganic layers is shorter and has more 3D-like characteristics in contrast to the (A) 2 A′ n-1 M n X 3n+1 2D perovskites. [20,[26][27][28][29][30]54] Although molecular-chemistry-dependent structure and optoelectronic properties of the AA′ n−1 M n X 3n+1 type 2D perovskites have been demonstrated, unfortunately, a series of low-n AA′ n−1 M n X 3n+1 perovskite devices reported currently shows poor performance.…”
Section: Introductionmentioning
confidence: 99%